UPAYA PENINGKATAN PRESTASI BELAJAR PENDIDIKAN AGAMA ISLAM DENGAN MENERAPKAN METODE JIGSAW LEARNING PADA SISWA KELAS V SD NEGERI 0701 ROTAN SOGO - Roslina Nasution (Al-Muaddib : Jurnal Ilmu-Ilmu Sosial & Keislaman, 2017)
This  study  is  an  effort  to  increase  learning  achievement  by applying  the  jigsaw  learning  method  on  Elementary  School  fifth grade  students  of  Rattan  Sogo  0701.  By  applying  the  jigsaw learning method is expected to improve the quality of teaching so that an increase learning achievement. Design of this research is the   subject   of   action   by   the   Elementary   School   fifth   grade students of Rattan Sogo 0701. Collecting data in this study done by  observation  and  written  tests  individuals  and  groups  at  the end  of  the  lesson.  Data  obtained  from  each  cycle  were  analyzed with  descriptive  qualitative  and  quantitative.  The  results  showed that  increased  student  involvement  which  have  an  impact  on student  achievement  has  increased  after  a  study  carried  out  by applying jigsaw learning method, with the following results: in the first cycle the average value of 6.21 grade increased to 6.72 in the second cycle and more increased again in the third cycle becomes 8.24